Digital Tools Supporting Teachers as Learning Designers: The Case of iCPeLDs for Designing Personalized Learning - Zalavra, Eleni; Papanikolaou, Kyparisia; Dimitriadis, Yannis; Sgouropoulou, Cleo; Liakopoulos, Vasileios (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2026)
Educational research has been promoting teaching as a design science, accounting for various digital tools that support teachers as learning designers. Learning Design (LD) tooling has employed pedagogical frameworks and models to explicitly stimulate and advance teachers’ design practices, such as inquiry-based, problem-based, blended, and collaborative learning. Remarkably, there seems to be a research gap concerning Personalized Learning (PL), as LD tools have implicitly addressed it by enabling teachers to design alternative sequences of learning activities. This paper presents the iCPeLDs tool, which focuses on supporting teachers in designing activities for PL. The tool’s novelty lies in incorporating a design framework for PL to scaffold teachers. Concretely, based on this design framework, the iCPeLDs tool (i) facilitates teachers to describe the learning context for PL, (ii) provides guidance that triggers teachers to address characteristics of their students’ profiles and apply personalization practices, and (iii) recommends peer-based practices by filtering and presenting how peers designed particular activities for PL. The paper also reports on a case study following a mixed-methods research design, which yields promising preliminary findings on the tool’s utilization in a teacher education context. The findings showcase the tool’s potential for supporting teachers as PL designers and provide valuable insights into LD tooling research.